Implementing the EU HTA regulation: Insights from semi-structured interviews on patient expectations, Belgian and European institutional perspectives, and industry outlooks - Desmet, Thomas; Brijs, Maud; Vanderdonck, Frank; Tops, Sven; Simoens, Steven; Huys, Isabelle (Frontiers in Pharmacology, 2024)
The goal of the Health Technology Assessment (HTA) Regulation 2021/2282 is to establish a more harmonized HTA framework, fostering member states cooperation and enabling equal patient access to innovative health technologies in Europe (1, 2). This research aimed to assess the impact of the regulation on national HTAs, the strategic implications for health technology developers, and its influence on price and reimbursement negotiations.A scoping literature review encompassing peer-reviewed literature as well as grey literature was conducted. Between February and March 2023, semi-structured interviews (n = 20) were performed with stakeholders from Belgian governmental institutions, European institutions, advanced therapy medicinal product developers, academics, and sickness funds. The interviews were analyzed using the framework analysis method (3).